One Slice at a Time: A Book Review of A Toolkit for Action Research - Suzanne Porath (Networks: An Online Journal for Teacher Research, 2012)
The foundation of research is the collection and analysis of data. Graduate students spend countless hours learning the ontology and epistemology of their chosen methodology. But, what about teachers who want to be more systematic with researching their own teaching practice and students but have limited time and resources? Many teachers choose to complete action research projects in their classrooms, but most textbooks only devote a short chapter to both the collection and analysis of data. In my experience, the discussions in these textbooks tend to be too short without enough models or templates to guide teacher-researchers through what can be an overwhelming amount of information. Susan M. Alber's A Toolkit for Action Research fills the gap with this short, practical book containing literally hundreds of frames, tools and templates to steer researchers through an action research project.